TECNOLOGÍA EDUCATIVA Y SU APORTE EN EL PROCESO DE ENSEÑANZA - APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO TÉCNICO DE LA UNIDAD EDUCATIVA MANUEL CÓRDOVA GALARZA, PERIODO ACADEMICO OCTUBRE 2023 – MARZO 2024. - GALARZA GALARZA, JOHNNY WILSON (2024)
The main purpose of this Final Report of the Investigative Project is to report the main characteristics found for the knowledge of educational technology and its contribution to the teaching-learning process of the technical high school students of the Manuel Córdova Galarza Educational Unit, in addition to knowing the acceptance of the possible use of technological resources and their Impact on the Teaching-Learning Process. The perfect development of the learning of technical high school students with the help of educational technology has directly to do with the knowledge and constant updating of teachers to apply new methodological strategies. Currently, at a national level, teachers use traditional acrylic blackboards to present their classes to students and this makes the student inactive, not very participatory, without paying due attention during class time, and therein lies the importance of teachers They are not trained and equipped with the necessary information to be able to handle this tool correctly through technological resources, which provides a lot of dynamic help when developing the subject when there is adequate knowledge of the use of this electronic tool. Keywords: Learning, technological resources, teaching strategies